Single‐ or Poly‐Crystalline Ni‐Rich Layered Cathode, Sulfide or Halide Solid Electrolyte: Which Will be the Winners for All‐Solid‐State Batteries?. Issue 21 (17th April 2021) - Han, Yoonjae; Jung, Sung Hoo; Kwak, Hiram; Jun, Seunggoo; Kwak, Hunho H.; Lee, Jong Hoon; Hong, Seung‐Tae; Jung, Yoon Seok
Abstract: Two newly emerging materials for application in all‐solid‐state batteries, namely, single‐crystalline Ni‐rich layered oxide cathode and halide solid electrolyte (SE), are of utmost interest because of their superior properties (good microstructural integrity and excellent electrochemical oxidation stability, respectively) to conventional polycrystalline layered oxides and sulfide SEs. In this work, four electrodes employing single‐ or polycrystalline LiNi0.88 Co0.11 Al0.01 O2 (NCA) and Li3 YCl6 or Li6 PS5 Cl0.5 Br0.5 are rigorously characterized by complementary analyses. It is shown that the synergy of employing cracking‐free single‐crystalline NCA and oxidation‐tolerable Li3 YCl6 can be achieved by considering intercoupled engineering factors that are prone to overlook, such as size, lightness, and mixing of particles. Accordingly, the highest level of performances in terms of discharge capacity (199 mA h g −1 at 0.1C), initial Coulombic efficiency (89.6%), cycling performance (96.8% of capacity retention at the 200th cycle), and rate capability (130 mA h g −1 at 4C) are demonstrated at 30 °C. Severe side reactions occurring at the Li6 PS5 Cl0.5 Br0.5 /NCA interfaces are also quantified and probed. Importantly, an overlooked but significant contribution of the side reaction of Li6 PS5 Cl0.5 Br0.5 to the detrimental electrochemo‐mechanical degradation of polycrystalline NCA is revealed for the first time by postmortem scanning electron microscopy and operando electrochemical pressiometry measurements. Abstract : The application of two newly emerging materials of cracking‐free single‐crystalline Ni‐rich layered oxide cathode and oxidation‐tolerable halide solid electrolyte for all‐solid‐state batteries leads to the highest level of performance in terms of cycling performance, capacity, and initial Coulombic efficiency. The detrimental electrochemo‐mechanical effects originating from side reactions of sulfide solid electrolytes are also revealed.